Extracellular vesicles highlight many cases of photoreceptor degeneration - Spencer, William J. (Frontiers in Molecular Neuroscience, 2023)
The release of extracellular vesicles is observed across numerous cell types and serves a range of biological functions including intercellular communication and waste disposal. One cell type which stands out for its robust capacity to release extracellular vesicles is the vertebrate photoreceptor cell. For decades, the release of extracellular vesicles by photoreceptors has been documented in many different animal models of photoreceptor degeneration and, more recently, in wild type photoreceptors. Here, I review all studies describing extracellular vesicle release by photoreceptors and discuss the most unifying theme among them–a photoreceptor cell fully, or partially, diverts its light sensitive membrane material to extracellular vesicles when it has defects in the delivery or morphing of this material into the photoreceptor’s highly organized light sensing organelle. Because photoreceptors generate an enormous amount of light sensitive membrane every day, the diversion of this material to extracellular vesicles can cause a massive accumulation of these membranes within the retina. Little is known about the uptake of photoreceptor derived extracellular vesicles, although in some cases the retinal pigment epithelial cells, microglia, Müller glia, and/or photoreceptor cells themselves have been shown to phagocytize them.